Clinical features of myocardial infarction and myocarditis in young adults: a retrospective study. Issue 6 (30th November 2012) - Pellaton, Cyril; Monney, Pierre; Ludman, Andrew James; Schwitter, Juerg; Eeckhout, Eric; Hugli, Olivier; Muller, Olivier
Abstract : Objectives: To evaluate the prevalence and clinical presentation of myocardial infarction (MI) and myocarditis in young adults presenting with chest pain (CP) and an elevated serum troponin I (TnI) to the emergency department (ED). Design: Retrospective, observational, single-centre study. Participants: All consecutive patients 18–40 years old admitted to the ED for CP with an elevated TnI concentration. Primary outcome measures: Prevalence of MI, myocarditis and the characterisation of clinical presentation. Results: 1588 patients between 18 and 40 years old were admitted to the ED with CP during 30 consecutive months. 49 (3.1%) patients with an elevated TnI (>0.09 μg/l) were included. 32.7% (16/49) were diagnosed with MI (11 ST-elevation myocardial infarction (STEMI) and 5 non-ST-elevation myocardial infarction (NSTEMI)) and 59.2% (29/49) with myocarditis. Compared with patients with myocarditis, MI patients were older (34.1±3.8 vs 26.9±6.4, p=0.0002) with more cardiovascular risk factors (mean 2.06 vs 0.69). Diabetes (18.8% vs 0%, p=0.0039), dyslipidaemia (56.2% vs 3.4%, p<0.0001) and family history of coronary artery disease (CAD) (37.5% vs 10.3% p=0.050) were associated with MI. Fever or recent viral illness were present in 75.9% (22/29) of patients with myocarditis, and in 0% of MI patients (p<0.0001). During follow-up, two patients with myocarditis were re-admitted for CP. Conclusions: In this study, 32.7% of patients <40-year-old admitted to an ED with CP and elevated TnI had a diagnosis of MI. Key distinctive clinical factors include diabetes, dyslipidaemia, family history of CAD and fever or recent viral illness.